2020
DOI: 10.1002/jsfa.10546
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of processing methods and oral mastication on the carotenoid bioaccessibility of restructured carrot chips

Abstract: BACKGROUND Carrot carotenoids are typically located in chromoplasts, forming a crystalline substructure. Cell walls and chromoplasts therefore constitute two major physical barriers to the release of carotenoids from the food matrix during digestion. The release of carotenoids from these physical barriers is supposed to be substantially affected by mechanical factors during food processing and oral mastication. Given the implications of this, the effects of four different processing procedures, and various mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Similar results with this study were presented in a recent study examining the bioaccessibility of carotenoids in carrot chips dried using a combination of instant pressure drop drying, hot air, and freeze drying [72]. As a result of the study, carotenoids in dried carrot chips were found to be more bioaccessible than those in fresh samples, although fresh carrots contained higher carotenoids than dried ones.…”
Section: Carotenoid Proflesupporting
confidence: 89%
“…Similar results with this study were presented in a recent study examining the bioaccessibility of carotenoids in carrot chips dried using a combination of instant pressure drop drying, hot air, and freeze drying [72]. As a result of the study, carotenoids in dried carrot chips were found to be more bioaccessible than those in fresh samples, although fresh carrots contained higher carotenoids than dried ones.…”
Section: Carotenoid Proflesupporting
confidence: 89%
“…[19][20][21] Factors that influence the digestive release and micellarization and bioaccessibility of carotenoids and chlorophylls have been reported from a number of in vitro models. 22 These include food/meal mineral content, 23 food matrix effects including cell wall integrity and subcellular structures, 24 mastication, 25,26 thermal processing, 27 and genotype. 28 These findings tend to be well aligned and correlated with in vivo studies that report that carotenoid absorption may vary across genotypes, different food processing methods and food matrices with processing having a generally positive effect on the overall bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…2 However, different processing methods may produce a negative impact on carrot texture (hardness) and nutrition quality (carotenoids). 3,4 Therefore, the development of better carrot processing methods to preserve texture and nutrition quality of carrot will be beneficial to the carrot industry.…”
Section: Introductionmentioning
confidence: 99%
“…Carrot processing usually passivates endogenous enzymes that are responsible for off‐flavor production and oxidation of nutrients, removal of raw/green flavors, color stabilization and prevention of microbial growth 2 . However, different processing methods may produce a negative impact on carrot texture (hardness) and nutrition quality (carotenoids) 3,4 . Therefore, the development of better carrot processing methods to preserve texture and nutrition quality of carrot will be beneficial to the carrot industry.…”
Section: Introductionmentioning
confidence: 99%